Treatment of Pseudomonas aeruginosa infectious biofilms: Challenges and strategies - Yin, Rui; Cheng, Juanli; Wang, Jingyao; Li, Panxin; Lin, Jinshui (Frontiers in Microbiology, 2022)
Pseudomonas aeruginosa, a gram-negative bacterium, is one of the top three major pathogens implicated in human opportunistic infection and a common cause of clinically persistent infections such as cystic fibrosis, urinary tract infections, and burn infections. The main reason for the persistence of P. aeruginosa infections is due to the ability of P. aeruginosa to secrete extracellular polymeric substances such as exopolysaccharides, matrix proteins, and extracellular DNA during invasion. These substances adhere to and wrap around bacterial cells to form a biofilm. Biofilm formation leads to multiple antibiotic resistance in P. aeruginosa, posing a significant challenge to conventional antibiotic therapeutic approaches. It has therefore become particularly important to develop anti-biofilm drugs. In recent years, a number of new alternative drugs have been developed to treat P. aeruginosa infectious biofilms, including antimicrobial peptides, quorum-sensing inhibitors, bacteriophage therapy, and antimicrobial photodynamic therapy (aPDT). This article briefly introduces the process and regulation of P. aeruginosa biofilm formation and reviews several traditional methods for biofilm treatment as well as current innovative treatment technologies with significant curative effects, so as to provide new directions for the treatment of P. aeruginosa biofilm infection.